Status of the Vibrational Theory of Olfaction - Hoehn, Ross D.; Nichols, David E.; Neven, Hartmut; Kais, Sabre (Frontiers in Physics, 2018)
The vibrational theory of olfaction is an attempt to describe a possible mechanism for olfaction which is explanatory and provides researchers with a set of principles which permit predictions allowing for structure-odor relations. Similar theories have occurred several times throughout olfactory science; this theory has again recently come to prominence by Luca Turin who suggested that inelastic electron tunneling is the method by which vibrations are detected by the olfactory receptors within the hose. This work is intended to convey to the reader the an up-to-date account of the vibrational theory of olfaction, both the historical iterations as well as the present iteration. This text is designed to give a chronological account of both theoretical and experimental studies on the topic, while providing context, comments and background where they were found to be needed.